Removal of calcium hydroxide from Weine Type II systems using photon-induced photoacoustic streaming, passive ultrasonic, and needle irrigation: a microcomputed tomography study (Journal of Applied Oral Science, 2016)
Objective This study compared the effectiveness of Er:YAG laser-activated irrigation (PIPS), passive ultrasonic irrigation (PUI) with EndoUltra and standard needle irrigation (SNI) in the removal of calcium hydroxide [Ca(OH)2] from the mesial roots of Weine Type II mandibular molars. Material and Methods Thirty mandibular molars were screened by µCT for the presence of mesial roots with complex intra-canal anatomy and a common apical foramen. The teeth were enlarged to a standardized 25/.06 preparation and filled with Ca(OH)2 paste. Specimens were divided into three groups (n=10) according to the technique used for Ca(OH)2 removal: PIPS, at 15 Hz and 20 mJ using a 9 mm long, 600 µm diameter tip; PUI using a 15/.02 tip; and SNI (30 Ga. side-vented needle). Equal volumes of 8.25% NaOCl and 17% EDTA were used in all groups. µCT was used to measure the initial amount of Ca(OH)2 present and to assess the residual volume of Ca(OH)2 following each irrigation protocol. Data were analyzed using Tukey HSD and Kruskal-Wallis tests (α=5%). Results The mean volume of Ca(OH)2 before removal was significantly higher in the coronal third than in the middle and apical third (p;0.05). PIPS (median 0%; IQR: 0-0) showed significant higher Ca(OH)2 removal in the apical third than PUI (median 100%, IQR: 85-100) and SNI (median 47%; IQR: 16-72) (p